The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/s2542-5196(20)30121-2
|View full text |Cite
|
Sign up to set email alerts
|

The environmental footprint of health care: a global assessment

Abstract: Background Health-care services are necessary for sustaining and improving human wellbeing, yet they have an environmental footprint that contributes to environment-related threats to human health. Previous studies have quantified the carbon emissions resulting from health care at a global level. We aimed to provide a global assessment of the wide-ranging environmental impacts of this sector.Methods In this multiregional input-output analysis, we evaluated the contribution of health-care sectors in driving env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
316
1
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(336 citation statements)
references
References 46 publications
(73 reference statements)
4
316
1
15
Order By: Relevance
“…For the MRIO-based results, previous work can provide context: an uncertainty analysis done for an earlier version of the UK MRIO model found that total UK consumer greenhouse gas emissions carried a relative SE of approximately 4-6%; previous health-care footprinting analyses found an SD of less than 5% globally and relative SEs of approximately 15% for China and 28% for Australia. 5,6,30 Qualitative sources of uncertainty are elaborated on in the Discussion.…”
Section: Uncertaintymentioning
confidence: 99%
“…For the MRIO-based results, previous work can provide context: an uncertainty analysis done for an earlier version of the UK MRIO model found that total UK consumer greenhouse gas emissions carried a relative SE of approximately 4-6%; previous health-care footprinting analyses found an SD of less than 5% globally and relative SEs of approximately 15% for China and 28% for Australia. 5,6,30 Qualitative sources of uncertainty are elaborated on in the Discussion.…”
Section: Uncertaintymentioning
confidence: 99%
“…Health systems are responsible for about 4.4% of the world's greenhouse gas emissions (Health Care Without Harm 2019). Healthcare is also responsible for a broader environmental impact of between 1% and 5% of the total global impact and more than 5% for some national impacts (Lenzen et al 2020). Healthcare thus contributes to illhealth through emissions, which cause climate change and other environmental impacts including air pollution (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare thus contributes to illhealth through emissions, which cause climate change and other environmental impacts including air pollution (e.g. through waste incineration) and water pollution (e.g., through pharmaceutical waste) (Eckelman and Sherman 2018;Health Care Without Harm 2019;Lenzen et al 2020). The health professions therefore have a moral obligation to take action to reduce the environmental impacts of healthcare provision.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio in Germany is 11.45% [78]. The healthcare causes global environmental impact ranges between 1% and 5% of the total global impacts and more than 5% for some national impacts based on Eora multiregional global supply-chain database contain detailed information on healthcare sectors that use to quantified the direct and indirect supply-chain environmental damage driven by demand for healthcare [79]. Similarly, obesity is associated with 20% greater GHG emissions relative to normal weight and 700 megatons per year of CO 2 equivalent which is about 1.6% of global GHG emission because of increase in oxidative metabolism, food intake, and fossil fuel use for transportation [80].…”
Section: Methodsmentioning
confidence: 99%